Towards a Digital Poetics - O'Sullivan, James (Palgrave Macmillan, 2019)
1. Introduction – 2. Digital Culture and the New Modernity – 3. Electronic Literature – 4. Interactivity and the Illusion of Choice – 5. Digital Materiality and the Politics of the Screen – 6. Towards a Digital Poetics We live in an age where language and screens continue to collide for creative purposes, giving rise to new forms of digital literatures and literary video games. Towards a Digital Poetics explores this relationship between word and computer, querying what it is that makes contemporary fictions like Dear Esther and All the Delicate Duplicates—both ludic and literary—different from their print-based predecessors
10.1007/978-3-030-11310-0
Keywords: Science; Digital Humanities; Humanities-Digital libraries; Literature; Modern-20th century; Digital media; Literature; Modern—21st century.; Philosophy and science.